2020
DOI: 10.3390/molecules25225387
|View full text |Cite
|
Sign up to set email alerts
|

Memory Effect in the Spatial Series Based on Diamond and Graphite Crystals

Abstract: To study the relation between the structure of a compound and its properties is one of the fundamental trends in chemistry and materials science. A classic example is the well-known influence of the structures of diamond and graphite on their physicochemical properties, in particular, hardness. However, some other properties of these allotropic modifications of carbon, e.g., fractal properties, are poorly understood. In this work, the spatial series (interatomic distance histograms) calculated using the crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This approach allowed us to calculate and analyze the fractal dimensions and Hurst coefficients of a number of molecular systems. [38,39] We found that the values of D depend on the structure of molecules and can be used to study a structure-property relationship. The aim of this work is to study the structural changes in the active site of hAChE during the formation of complexes with a number of ligands by analyzing their fractal dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed us to calculate and analyze the fractal dimensions and Hurst coefficients of a number of molecular systems. [38,39] We found that the values of D depend on the structure of molecules and can be used to study a structure-property relationship. The aim of this work is to study the structural changes in the active site of hAChE during the formation of complexes with a number of ligands by analyzing their fractal dimensions.…”
Section: Introductionmentioning
confidence: 99%